Gerakan literasi sekolah terstruktur untuk mengembangkan keterampilan abad 21 - Kusmiati, Kusmiati (2018)
Revolusiindustri4.0diduniatentumembawadampakpadakemajuanilmupengetahuandanteknologi.Kemajuanitutentunyaharusdiikutidengankualitaspendidikan.OlehkarenaitudiperlukanpembelajarandanSDMyangmampumengembangkanketerampilanberpikirkritiskreatifdaninovatifkolaboratifdankomunikatifbagipesertadidik.Halitutentusajabisadilaluimelaluikemampuanliterasiyangbaik.Kemampuanliterasiyangbaikmampumeningkatkanketerampilanabad21(keterampilanberpikirkritiskreatifdaninovatifkolaboratifdankomunikatif)dalammenghadapaierapersainganglobal.Untukitulahgerakanliterasisekolahyangdilaksanakansecaraterstrukturmampumengembangkanketerampilantersebut.KataKunciGerakanLiterasiSekolahTerstrukturKeterampilanAbad21